The effect of attentional bias modification on positive affect dynamics - Kraft, B; Bø, R; Harmer, CJ; Landrø, NI (Nature Research, 2024)
Negative attentional bias and alterations in positive affect dynamics constitute emotional vulnerability to depression. Attentional bias modification (ABM) aims to reduce emotional vulnerability to depression by fostering attentional deployment towards positive stimuli. In this randomized controlled trial, we examined whether ABM leads to changes in positive affect dynamics in a sample with an emotional vulnerability to depression (N = 65). Affect dynamics were measured based on experience sampling data gathered 14 days before and after ABM. During ABM, participants paid attention to pairs of emotional faces and responded to dots that were appearing in their place. There was an 87% chance for the dots to appear in place of the relatively more positive face, with the purpose to implicitly foster attentional focus on positive stimuli. In the control condition, there was a 50% chance of the dots to appear in place of the positive stimuli. Results showed that the lag-1 autocorrelation of affect (“inertia”) increased within the ABM group and decreased in the control group, but the findings were not robust and it was unclear whether ABM was the cause. There were no changes in the other affect dynamics indices. Improvements in depression during ABM were not associated with changes in affect dynamics, and affect dynamics post ABM did not predict depression symptoms six months later. In conclusion, the study showed no clear effect of ABM on affect dynamics.